Compendium of supply and use tables for selected economies in Asia and the Pacific. (Metro Manila, Philippines Asian Development Bank, 2017)
Supply and use tables (SUTs) are an integrated statistical estimation and economic analysis model that facilitates the compilation of more reliable, consistent, and internationally comparable estimates of key economic statistics such as gross domestic product. The improved and more detailed statistics are expected to provide a better basis for measuring economic output and growth; facilitating informed policy making; and monitoring progress toward the Sustainable Development Goals (SDGs), relating especially to poverty alleviation, economic growth, technological progress, and industrial and infrastructure development.
Keywords: Economics; Electronic books